2015
DOI: 10.1055/s-0035-1560066
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of Isoindole Derivatives Containing an Azetidinone Ring

Abstract: Isoindole derivatives containing an azetidin-2-one moiety were prepared from phthalic anhydride by an approach that involves a [2π+2π] cycloaddition of an imine to a novel ketene generated in situ, and an electrocyclic reaction of a zwitterionic intermediate. The reactions were highly stereoselective and trans-β-lactams were obtained as the sole observed products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…(114) in the presence of glacial acetic acid in reuxing dioxane (Scheme 40). 151 Simijonovic in 2020 described green aqua-mediated synthesis of benzamide-dioxoisoindoline derivatives (117) via the reaction of PA and benzoyl hydrazides (116) at 80 °C under ultrasonic irradiation. All compounds were subjected to experimental determination of their antioxidative potential.…”
Section: Applications Of Pa In Twocomponent Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(114) in the presence of glacial acetic acid in reuxing dioxane (Scheme 40). 151 Simijonovic in 2020 described green aqua-mediated synthesis of benzamide-dioxoisoindoline derivatives (117) via the reaction of PA and benzoyl hydrazides (116) at 80 °C under ultrasonic irradiation. All compounds were subjected to experimental determination of their antioxidative potential.…”
Section: Applications Of Pa In Twocomponent Reactionsmentioning
confidence: 99%
“…The reaction was found to be highly stereoselective, and the trans -isomers of (E) were obtained as the only products ( Scheme 15 ). 117 …”
Section: Applications Of Pa In Two-component Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that activation of carboxylic acid with Mukaiyama’s reagent is superior to the corresponding acid chloride for the in situ generation of ketene and subsequent cyclization . Mukaiyama’s reagent (2-chloro- N -methyl­pyridinium iodide) is an effective reagent to generate ketenes in situ for subsequent [2 + 2] cycloadditions with alkenes, allenes, aldehydes, imines, and hydrazones . Although initial studies on the acid 3c with Mukaiyama’s reagent failed to yield desired intramolecular cycloadduct 4a , when the phenylthio-substituted acid 3d and 3f were added to a solution of Mukaiyama’s reagent and Et 3 N in refluxing CH 3 CN, cycloadducts 4b and 4f were obtained as single diastereomers in 70% and 62% yields, respectively (entries 4 and 6, Table ).…”
mentioning
confidence: 99%